Neural Oscillations Associated With Auditory Duration Maintenance in Working Memory in Tasks With Controlled Difficulty - Yu, Xiaolin; Chen, Youguo; Luo, Ting; Huang, Xiting (Frontiers in Psychology, 2020)
The neural representation of the external events duration in working memory remains to be understood. It has been reported that there were different neural representations below and above 3s / 2s for visual / auditory duration, respectively. However, these studies had limitations in experimental design, i.e. the interference of task difficulty was not assessed. Consequently, the results of these studies require verification. In the present study, we eliminated these limitations using an exploratory experiment in which the probe stimulus conditions were reset, while the other settings remained similar to those used in previous studies. In the exploratory experiment, we found that accuracy and reaction times were comparable among all the four duration conditions, suggesting that task difficulty was accurately matched. In the formal experiment, theta and alpha oscillations were examined using electroencephalogram recordings during the maintenance of the auditory duration in working memory, after removing the interference of task difficulty. Electroencephalogram results indicated that there were no significant differences in theta band power among different length of durations retained in working memory, whereas the alpha band power was significantly lower in the 3-s and 4-s duration conditions than in the 1-s and 2-s conditions. The findings suggest that different internal representations of auditory durations above and below the 2-s threshold are maintained in working memory. Also, our study provides evidence that the duration representation segmentation is associated with the length of the auditory duration retained in working memory, but not with task difficulty.